Menyoal Bisnis Kosmetik Bersertifikat Halal (Analisis Undang-Undang Nomor 33 Tahun 2014 Tentang Jaminan Prodak Halal) (Universitas Islam Negeri Sunan Kudus, 2022)
This study aims to determine the achievements of the halal cosmetic product business, the challenges of halal product guarantee through analysis of halal product guarantee regulations. This study uses a descriptive approach with qualitative data that is conceptual in nature by linking Value chain theory, action and mirror theory. The results show that the halal-certified cosmetic business is a fairly competitive business for business people. However, there are cosmetic brands that are quite large and are found to contain non-halal ingredients. The trend of the halal-certified cosmetic business is in synergy with LPPOM-MUI, the MUI Fatwa Commission and BPOM in issuing Halal Label certificate licensing for producers who want their products to be halal-certified. In addition to the large opportunity for selling halal cosmetic products in Indonesia, the use and selection of raw materials that are free from haram ingredients is something that cosmetic manufacturers must pay attention to. This has become the testing power of Law Number 33 of 2014 concerning Guaranteed Halal Products to consistently provide legal certainty and protection for the community based on belief as stated in Article 28 and 29 of the 1945 Constitution.